2004
DOI: 10.1002/humu.20070
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive molecular screening of theFBN1gene favors locus homogeneity of classical Marfan syndrome

Abstract: In order to estimate the contribution of mutations at the fibrillin-1 locus (FBN1) to classical Marfan syndrome (MFS) and to study possible phenotypic differences between patients with an FBN1 mutation vs. without, a comprehensive molecular study of the FBN1 gene in a cohort of 93 MFS patients fulfilling the clinical diagnosis of MFS according to the Ghent nosology was performed. The initial mutation screening by CSGE/SSCP allowed identification of an FBN1-mutation in 73 patients. Next, sequencing of all FBN1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
127
3
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(155 citation statements)
references
References 21 publications
18
127
3
7
Order By: Relevance
“…This pseudoexon was predicted to lead to a premature termination codon at the beginning of the pseudoexon. Studies have identified FBN1 mutations in 91% of MFS patients, raising the possibility of cryptic FBN1 mutations not identified by current genomic sequencing approaches, or suggesting that mutations in other genes such as TGFBR2 may lead to classic MFS (Loeys et al 2004). The data presented here confirm that cryptic FBN1 mutations, such as those that generate pseudoexons, can lead to MFS.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…This pseudoexon was predicted to lead to a premature termination codon at the beginning of the pseudoexon. Studies have identified FBN1 mutations in 91% of MFS patients, raising the possibility of cryptic FBN1 mutations not identified by current genomic sequencing approaches, or suggesting that mutations in other genes such as TGFBR2 may lead to classic MFS (Loeys et al 2004). The data presented here confirm that cryptic FBN1 mutations, such as those that generate pseudoexons, can lead to MFS.…”
Section: Introductionsupporting
confidence: 63%
“…Direct sequencing of the exons and flanking introns in the remaining 20 patients was followed by Southern blot analysis for large deletions and insertions. This study identified FBN1 mutations in 91% of MFS patients (Loeys et al 2004). A study of direct DNA sequencing of the exons and flanking introns of FBN1, FBN2, TGFBR1, and TGFBR2 on 49 MFS or MFS-suspected patients identified FBN1 mutations in 55% of patients and TGFBR1 and TGFBR2 mutations in 6% of patients [Sakai et al 2006].…”
Section: Discussionmentioning
confidence: 72%
“…In classical MFS the incidence of ectopia lentis was significantly higher in patients harboring cysteine substitutions in the cbEGF-like modules than in patients with premature termination codon (PTC) mutations (Arbustini et al 2005;Biggin et al 2004;Loeys et al 2004;Rommel et al 2005;Schrijver et al 2002). Furthermore, isolated or predominant ectopia lentis is frequently associated with cysteine substitutions Comeglio et al 2002), suggesting that cysteine residues may have a critical function in suspensory ligaments of the eyes, as previously described (Rommel et al 2005).…”
Section: Pathogenesis Of Marfan Syndromementioning
confidence: 63%
“…More than 600 FBN1 mutations are registered in the UMD-FBN1 database for MFS and its associated disorders (http:// www.umd.be:2030/) . The mutation detection rate of FBN1 in MFS varies among studies, ranging from 9% to 91% (Katzke et al 2002;Loeys et al 2004;Tynan et al 1993). This variability could be explained, in part, by the different techniques used, but the most significant influencing factor is likely to be sample bias.…”
Section: Fbn1 Mutation-related Disordersmentioning
confidence: 99%
“…Therefore, from a management perspective, the distinction from MFS is neither ambiguous nor unimportant. Comprehensive mutation analysis of fibrillin-1 in 93 consecutive individuals referred with classic MFS identified 86 mutations 17 . We sequenced TGFBR1 and TGFBR2 in the other seven individuals and found no mutations (data not shown).…”
mentioning
confidence: 99%